2D molecular crystal lattices: advances in their synthesis, characterization, and application. Issue 41 (29th August 2019) - Solomos, Marina A.; Claire, F. James; Kempa, Thomas J.
Abstract : 2D molecular crystal lattices form a compelling class of 2D materials with synthetically-tunable properties and the potential to spawn a new generation of devices for optoelectronics and energy sustainability. Abstract : This review identifies how recent advances in controlling the structure and properties of MOF and COF thin films can be used to establish 2D molecular crystals as a new material platform with key applications in catalysis, sensing, separations, and electronics. In addition to summarizing research efforts surrounding the synthesis, characterization and utilization of 2D and thin film MOFs and COFs, this review identifies exigent challenges in their development, and motivates the search for new synthetic methods, advanced analytical techniques, and creative applications. Ultimately, 2D molecular lattices, be they 2D MOFs or COFs, are a compelling platform through which to discover new and emergent properties and to expand the library of 2D materials.